Francisco Adolfo de Varnhagen, a narrativa do episódio da invasão holandesa e o mito fundacional do Brasil : fato, temporalidades e sujeitos históricos e as suas ressonâncias no ensino de história - Marinho, Marcela Irian Angélica Machado (2014)
The research presented here fits into the contemporary research on the history of Brazilian historiography, where it was possible to identify and understand patterns in the writing of history commitment to the ideal of the nation during the Second Empire in the nineteenth century, from the deconstruction the plots of the narrative of the episode the invasion and expulsion of the Dutch in colonial Brazil (seventeenth century) elaborated by the historian-diplomat São Paulo Francisco Adolfo de Varnhagen (1816-1878), the work Historia das Lutas contra os Hollandezes no Brasil desde 1624 a 1654, published in 1871. such work published in 1871, with a second edition in 1872, was written in the heat of the Silver and conflicts in order to remind the Brazilians involved in the war against Paraguay (was in 1866), that his countrymen have had faced yet another country colony - Dutch invaders - and that would have been victorious.